2008
DOI: 10.1002/art.23514
|View full text |Cite
|
Sign up to set email alerts
|

Patients with pulmonary tuberculosis are frequently positive for anti–cyclic citrullinated peptide antibodies, but their sera also react with unmodified arginine‐containing peptide

Abstract: Objective. The anti-cyclic citrullinated peptide (anti-CCP) enzyme-linked immunosorbent assay (ELISA) has high sensitivity and specificity for rheumatoid arthritis (RA). However, detection of anti-CCP in patients with active pulmonary tuberculosis (TB) has recently been reported. To determine whether this activity was specific for the citrullinated residue, the specificity of anti-CCP-positive sera for CCP versus that for unmodified arginine-containing peptide (CAP) was examined in patients with TB and compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
64
1
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(71 citation statements)
references
References 15 publications
5
64
1
1
Order By: Relevance
“…The control group consisted of healthy subjects (n=30), systemic lupus erythematosus (SLE) patients (n=35) and systemic sclerosis (SSc) patients (n=28). In the SLE group, the presence of active tuberculosis (TB) was also noted because of recent reports of an association between aCCP and TB [13,14], coupled with the frequent occurrence of TB in our SLE patients [15].…”
Section: Methodsmentioning
confidence: 83%
“…The control group consisted of healthy subjects (n=30), systemic lupus erythematosus (SLE) patients (n=35) and systemic sclerosis (SSc) patients (n=28). In the SLE group, the presence of active tuberculosis (TB) was also noted because of recent reports of an association between aCCP and TB [13,14], coupled with the frequent occurrence of TB in our SLE patients [15].…”
Section: Methodsmentioning
confidence: 83%
“…Kakumanu et al (11) reported that anti-unmodified arginine-containing peptide (anti-CAP) levels were higher in patients with active TB infections compared to RA patients. While the anti-CAP/anti-CCP ratio was >2 in 94% of patients with RA, the same ratio was observed in only 22% of patients with TB.…”
Section: Discussionmentioning
confidence: 99%
“…While the anti-CAP/anti-CCP ratio was >2 in 94% of patients with RA, the same ratio was observed in only 22% of patients with TB. Thus, it was concluded that the anti-CCP/anti-CAP ratio could be used for differentiating TB arthritis from RA (11).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…14 The diagnosis of chronic HBV and HCV infections is based on the HBsAg and anti-HCV positivity persisting for more than 6 months. 2 Certain characteristics of chronic HBV and HCV infections are similar to those of rheumatic and renal diseases. Any of the symptoms of chronic HBV and HCV infections such as arthralgia, peripheral arthritis or laboratory findings like elevated acute phase reactants including C-reactive protein (CRP), erythrocyte sedimentation rate (ESR) and positivity of RF are important markers for the diagnosis of inflammatory rheumatic diseases.…”
mentioning
confidence: 99%